2013
DOI: 10.1182/blood.v122.21.3513.3513
|View full text |Cite
|
Sign up to set email alerts
|

Targeting The PI3K/AKT Pathway To Inhibit Platelet Activation and Thrombus Formation

Abstract: The phosphatidylinositol 3' –kinase (PI3K)-Akt signaling pathway has been shown to be critical in modulating platelet function and increasing number of studies have been focusing on the development of PI3K inhibitors to modulate platelet function. We recently identified a novel small molecule compound S14161, namely 8-ethoxy-2-(4-fluorophenyl)-3-nitro-2H-chromene, displaying potent antileukemia and antimyeloma activity via inhibition of the PI3K pathway (Mao et al, Blood, 2011, 117:1986). In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been observed that dephosphorylation and inactivation of PI3K by ginsenoside Ro attenuates fibrinogen binding to glycoprotein IIb/IIIa, reflecting the intensification of thrombus in human platelets [ 52 ]. Also, it has been demonstrated that PI3K/AKT signaling inhibition by 8-ethoxy-2-(4-fluorophenyl)-3-nitro-2H-chromene leads to inhibition of fibrinogen binding of single platelet and thrombus formation in cultured human platelets [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that dephosphorylation and inactivation of PI3K by ginsenoside Ro attenuates fibrinogen binding to glycoprotein IIb/IIIa, reflecting the intensification of thrombus in human platelets [ 52 ]. Also, it has been demonstrated that PI3K/AKT signaling inhibition by 8-ethoxy-2-(4-fluorophenyl)-3-nitro-2H-chromene leads to inhibition of fibrinogen binding of single platelet and thrombus formation in cultured human platelets [ 53 ].…”
Section: Introductionmentioning
confidence: 99%